Intravenous lipid emulsion as a treatment of sinus tachycardia induced by synthetic cannabinoid intoxication: two case reports - İzci, Filiz and İzci, Vedat and İzci, Servet and Çiftci, Elvan and İris Koç, Merve and; ci, Rabia and; epe, Engin Emrem (Journal of Dependence, 2015)
Synthetic cannabinoid usage has been gradually increasing. Intoxication related to synthetic cannabinoid usage is becoming more common, and life-threatening cases are encountered in the general hospitals and psychiatry emergency services. Unlike cannabis, acute intoxication symptoms of synthetic cannabinoid are similar to the effects of stimulants and sympathomimetic usage. During synthetic cannabinoid usage, side effects such as diaphoresis, nausea, vomiting, appetite changes, hyper/hypotensi-on, chest pain, tachycardia/bradycardia, respiratory depression, confusion, psychomotor agitation, somnolence and sedation can be seen. The most common physical side effect is tachycardia. In this report, two cases of sinus tachycardia induced by synthetic cannabinoid usage, which were treated with intravenous lipid emulsion, were discussed.